Production of small cysteine‐rich effector proteins in Escherichia coli for structural and functional studies. (12th April 2016) - Zhang, Xiaoxiao; Nguyen, Neal; Breen, Susan; Outram, Megan A.; Dodds, Peter N.; Kobe, Bostjan; Solomon, Peter S.; Williams, Simon J.
Summary: Although the lifestyles and infection strategies of plant pathogens are diverse, a prevailing feature is the use of an arsenal of secreted proteins, known as effectors, which aid in microbial infection. In the case of eukaryotic filamentous pathogens, such as fungi and oomycetes, effector proteins are typically dissimilar, at the protein sequence level, to known protein families and functional domains. Consequently, we currently have a limited understanding of how fungal and oomycete effectors promote disease. Protein biochemistry and structural biology are two methods that can contribute greatly to the understanding of protein function. Both techniques are dependent on obtaining proteins that are pure and functional, and generally require the use of heterologous recombinant protein expression systems. Here, we present a general scheme and methodology for the production and characterization of small cysteine‐rich (SCR) effectors utilizing Escherichia coli expression systems. Using this approach, we successfully produced cysteine‐rich effectors derived from the biotrophic fungal pathogen Melampsora lini and the necrotrophic fungal pathogen Parastagonospora nodorum . Access to functional recombinant proteins facilitated crystallization and functional experiments. These results are discussed in the context of a general workflow that may serve as a template for others interested in understanding the function of SCR effector(s) from their plant pathogen(s) of interest.